The Runaround: Punishment, Welfare, and Poverty Survival after Prison. (28th June 2019) - Halushka, John M
Abstract: Based on 17 months of ethnographic fieldwork and 45 in-depth interviews with formerly-incarcerated men, this article explores how former prisoners navigate criminal justice and welfare bureaucracies in their daily lives. Formerly-incarcerated men must repeatedly engage with parole, public assistance agencies, transitional housing facilities, and community-based service providers to maintain freedom and access food, shelter, and rehabilitative services. Accessing resources requires the men simultaneously to manage multiple, overlapping entanglements across a fragmented network of bureaucracies. This runaround exacerbates the stress of poverty, breeds distrust of state authorities, and, in some cases, precipitates recidivism. Former prisoners learned how to cope with the runaround by treating systems navigation as a full-time occupation, but these skills did not translate into long-term economic security. Most study participants recurrently cycled between low-wage jobs, transitional housing facilities, and public assistance programs for years after release. This article illustrates the need to theorize prisoner reentry as a process that unfolds across a network of criminal justice and welfare bureaucracies and demonstrates how formerly-incarcerated men experience citizenship not only through coercive encounters with the criminal justice system but also through their simultaneous entanglements with safety-net bureaucracies.